Sequencing of Cladosporium sphaerospermum, a Dematiaceous Fungus isolated from blood culture - Ng, K.P.; Yew, S.M.; Chan, C.L.; Soo-Hoo, T.S.; Na, S.L.; Hassan, H.; Ngeow, Y.F.; Hoh, C.C.; Lee, K.W.; Yee, W.Y. (2012)
Cladosporium sphaerospermum is one of the most widely distributed allergens causing serious problems in patients with respiratory tract disease. We report the 26,644,473-bp draft genome sequence and gene annotation of C. sphaerospermum UM843. Analysis of the genome sequence led to the finding of genes associated with C. sphaerospermum's melanin biosynthesis, allergens, and antifungal drug resistance.